﻿Tecnica di esecuzione di alcuni affreschi della Farnesina - Varoli-Piazza, Rosalia (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 1985)
The epochal restoration of the entire interior decoration of the Villa Farnesina, which is currently underway by the Istituto Centrale del Restauro, is revealing the identification of a rich variety of technical issues. Specifically, the campaign in the Sala delle Prospettive, undertaken between 1976 and 1983, focuses on several new matters relating to the Renaissance tradition of Roman fresco painting. Chemical analysis of the intonaco coupled with the detailed reconstruction of the giornate results in a fascinating reevaluation of the frescoes themselves relating to their manufacture. The inspection of the surfaces reveals the exact manner in which the frescoes were constructed, making use of cartoni and spolveri, or on occasion of no final preparatory drawings at all. Secondly, the restoration of 14 pilasters a grottesche in the Sala della Galatea clearly demonstrates the exclusive use of spolveri. The remaining 11 pilasters will be cleaned in 1985. Once this campaign in the room is completed, then the exact nature of this early 16th-century cycle, with its 19th-century ‘restorations,’ will be identifiable, and will subsequently be integrated with the restoration of the Loggia di Psiche, which will commence in 1985.